Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2021
DOI: 10.1080/10447318.2021.1886484
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Touch Button Interface on In-Vehicle Information Systems Usability

Abstract: We analyzed the button input method of infotainment systems as part of the in-vehicle information system (IVIS) interface and related research. As IVIS becomes more complex and the need for drivervehicle interaction increases, so does the potential risk that accompanies driver input. In this study, we propose to analyze the influence of the touch button shape, background, button and text color combination, and the presence/absence of a button border on the usability of the button input operation, which has not… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(5 citation statements)
references
References 62 publications
1
4
0
Order By: Relevance
“…Finally, similar to attentional resources, in terms of lateral driving performance, a clear advantage was demonstrated when using CIM to perform the secondary task compared with FTIM. This finding was consistent with previous studies [31,32]. The TLC when performing the secondary task using CIM was 1.89 s longer than when using FTIM.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Finally, similar to attentional resources, in terms of lateral driving performance, a clear advantage was demonstrated when using CIM to perform the secondary task compared with FTIM. This finding was consistent with previous studies [31,32]. The TLC when performing the secondary task using CIM was 1.89 s longer than when using FTIM.…”
Section: Discussionsupporting
confidence: 93%
“…Subsequently, Zeng [31] studied the impact of conventional button-based interaction modes, voice interaction modes, and touch screen interaction modes on driving safety from the perspective of driving safety and found that CIM had the least impact on driving safety, and that the touchscreen interaction mode had the greatest impact on driving safety. Moreover, a number of studies have noted that touchscreen interaction modes without nonvisual feedback have worse task performance than traditional physical button interaction modes [32,33].…”
Section: Research On the Impact Of Secondary Tasks On Resourcementioning
confidence: 99%
“…The findings of this study can be utilized as the basis for redesigning icons, particularly for icons related to COVID-19 prevention measures [ 48 ]. Furthermore, the approach can also be applied and extended for evaluating other medical icons [ 49 , 50 ], safety icons, disaster-related prevention icons [ 51 ], transportation-related icons [ 52 , 53 ], and even entertainment-related icons [ 54 , 55 , 56 , 57 , 58 ].…”
Section: Discussionmentioning
confidence: 99%
“…When the legibility of information is low, the users’ reading time will increase ( Naujoks et al, 2019 ). Existing studies on interface color include the color contrast between buttons and text ( Jung et al, 2021 ) and the influence of interface background color on user emotion ( Cheng et al, 2019 ). As for the color study of buttons, Huang found that the color combination of the graphics and background in the button icon affected the visual search performance.…”
Section: Related Workmentioning
confidence: 99%